Assessments of Proliferation Capacity and Viability of New Zealand Rabbit Peripheral Blood Endothelial Progenitor Cells Labeled with Superparamagnetic Particles - Xiao-Li Mai (Cell Transplantation, 2009)
Magnetic resonance imaging (MRI) has proven to be effective in tracking the distribution of transplanted stem cells to target organs by way of labeling cells with superparamagnetic iron oxide particles (SPIO). However, the effect of SPIO upon labeled cells is still unclear on a cellular level. With this study, the proliferation and viability of New Zealand rabbit peripheral blood endothelial progenitor cells (EPCs) labeled with SPIO were evaluated and in vitro images were obtained using a 1.5 T MR scanner. Mononuclear cells (MNCs) were isolated from peripheral blood of the adult New Zealand rabbit and cultured in fibronectin-coated culture flasks, in which EPCs were identified from cell morphology, outgrowth characteristics, and internalization of DiI-Ac-LDL and binding to FITC-UEA I. EPCs were incubated with the self-synthesized poly-L-lysine-conjugated SPIO (PLL-SPIO) particles in a range of concentrations. The prevalence of iron-containing vesicles or endosomes in the cytoplasm of labeled cells was confirmed with Prussian blue staining and transmission electron microscopy. Tetrazolium salt (MTT) assay, cell apoptosis, and cycle detection were assessed to evaluate proliferation and function of various concentrations, magnetically labeled EPCs. The quantity of iron per cell was determined by atomic absorption spectrometry. The cells underwent MRI with different sequences. The result showed that rabbit EPCs were efficiently labeled with the home synthesized PLL-SPIO. There was found to be no statistically significant difference in the MTT values of light absorption measured on the third and fifth days. Between labeled and unlabeled cells, there were also no aberrations found in the cell cycles, apoptosis, or growth curves. The atomic absorption spectrophotometer showed that the intracellular content of Fe decreased as more time elapsed after labeling. The labeled EPCs demonstrated a loss of MRI signal intensity (SI) when compared with the SI of unlabeled cells. These signal changes (ΔSI) were visible when cells were labeled with more than 5 × 10 4 /ml of SPIO. The change in SI corresponded to the amount of iron in the EPCs, which reached a maximum at T 2 * WI. These data demonstrate that EPCs from the peripheral blood of the New Zealand rabbit can be effectively labeled with self-synthesized PLL-SPIO with minimal effects on cell proliferation and activity. Magnetically labeled EPCs can be imaged at 1.5 T MR and can therefore be used as an MR tracker of implanted EPCs.